1991
DOI: 10.1007/bf00352328
|View full text |Cite
|
Sign up to set email alerts
|

The recombinant congenic strains—a novel genetic tool applied to the study of colon tumor development in the mouse

Abstract: The development of tumors in mice is under multigenic control, but, in spite of considerable efforts, the identification of the genes involved has so far been unsuccessful, because of the insufficient resolution power of the available genetic tools. Therefore, a novel genetic tool, the RC (Recombinant Congenic) strains system, was designed. In this system, a series of RC strains is produced from two inbred strains, a "background" strain and a "donor" strain. Each RC strain contains a different small subset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 50 publications
1
42
0
Order By: Relevance
“…Pilot studies using AOM showed the same difference in colon tumor susceptibility between the two parental strains, BALB/c and STS, and the RC strain CcS-19 as reported previously for DMH-induced tumors (Moen et al, 1992;Van Wezel et al, 1996). The number and size of the AOM-induced colon tumors, however, was markedly higher.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Pilot studies using AOM showed the same difference in colon tumor susceptibility between the two parental strains, BALB/c and STS, and the RC strain CcS-19 as reported previously for DMH-induced tumors (Moen et al, 1992;Van Wezel et al, 1996). The number and size of the AOM-induced colon tumors, however, was markedly higher.…”
supporting
confidence: 77%
“…Treatment of BALB/c and CcS-strain mice with repeated injections of the carcinogen 1,2-dimethylhydrazine (DMH) induces multiple colonic adenomas, that are benign, even if they are very large (Moen et al, 1991). Five loci affecting susceptibility to chemically induced colon cancer, Scc1-Scc5, were previously identified using 192 F 2 mice between susceptible RC strain CcS-19 and BALB/c.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the Dcc remains as a candidate for Par2, although we previously demonstrated by loss of heterozygosity analysis that the Dcc locus may not be involved in mouse lung tumorigenesis as a tumor suppressor gene (Obata et al, 1996). There are two previous reports on restriction fragment length polymorphism of the mouse Dcc gene: alleles of C57BL and Mus spretus (Justice et al, 1992) and those of BALB/c and STS/A (Moen et al, 1992) can be distinguished. We are currently searching for such polymorphism between BALB and C57BL alleles of the Dcc gene, in order to determine whether it can be excluded as a candidate by genotyping R 7 B7 and R 7 B10 recombinants.…”
Section: Discussionmentioning
confidence: 99%
“…17,[19][20][21][22][23][24][25][26][27] A series of RC strains comprises approximately 20 homozygous strains, each of which contains on average 87.5% genes of a common background strain and 12.5% of a common donor strain. 26,28 In this way, the RC system transforms a multigenic difference into a set of mono-or oligogenic differences and hence offers higher resolution power in mapping the quantitative trait loci and detecting their mutual interactions than the standard genetic methods. The RC system has been used most successfully to map genes in colon tumor susceptibility.…”
Section: Polymorphisms Of Both Adam33 and Spink5mentioning
confidence: 99%